Knowledge and attitudes toward female genital cutting among West African male immigrants in New York City. Issue 5 (4th May 2017) - Akinsulure-Smith, Adeyinka M.; Chu, Tracy
ABSTRACT: In this project, we explored knowledge and attitudes toward female genital cutting (FGC) in a survey of 107 West African immigrants, including 36 men. Men in this study were as knowledgeable about the health consequences of FGC as women, though with a less nuanced understanding. They also rejected the practice at rates comparable to women. Despite this knowledge and rejection of FGC, most men did not express a personal preference for women with or without FGC in intimate relationships. Future research and interventions must explore men's opposition to FGC and emphasize the impact of FGC on their partners' gynecological and reproductive health.